The Application of Electrothermal Averaged Models to Analyze the Distribution of Power Losses in the Components of DC-DC Converters - Krzysztof Górecki; Paweł Górecki (Energies)
This paper analyzes the possibility of using averaged models to analyze the distribution of power losses in the components of a DC-DC converter including a power module. An electrothermal averaged model of a buck converter including the IGBT module was formulated. This model takes into consideration conduction and switching losses in the mentioned components, the self-heating phenomenon in each component, and mutual thermal coupling between their sub-components. It is designed for SPICE software (version PSPICE A/D 17.4). Its correctness was verified experimentally, and the results obtained were compared with the results of analyses performed with the use of PLECS software and the IGBT module model proposed by the manufacturer. The proposed model’s results show very good accuracy. Through the use of the proposed model, the dependences of the components of power losses and the case temperature of the IGBT module and the inductor on parameters describing the control signal and load of this converter were determined. The distribution of power losses in the converter components was analyzed for selected operating conditions of the buck converter. On the basis of the results obtained, some recommendations were formulated for designers of such DC-DC converters.